2017
DOI: 10.1002/2017ja023876
|View full text |Cite
|
Sign up to set email alerts
|

Electron density extrapolation above F2 peak by the linear Vary‐Chap model supporting new Global Navigation Satellite Systems‐LEO occultation missions

Abstract: The new radio‐occultation (RO) instrument on board the future EUMETSAT Polar System‐Second Generation (EPS‐SG) satellites, flying at a height of 820 km, is primarily focusing on neutral atmospheric profiling. It will also provide an opportunity for RO ionospheric sounding, but only below impact heights of 500 km, in order to guarantee a full data gathering of the neutral part. This will leave a gap of 320 km, which impedes the application of the direct inversion techniques to retrieve the electron density prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 38 publications
2
35
1
Order By: Relevance
“…Also, our results are supported by the need in increase of the electron density scale height above F2‐layer peak recently confirmed with direct radio occultation GPS measurements (Hernández‐Pajares et al, ; Olivares‐Pulido et al, ).…”
Section: Resultssupporting
confidence: 88%
“…Also, our results are supported by the need in increase of the electron density scale height above F2‐layer peak recently confirmed with direct radio occultation GPS measurements (Hernández‐Pajares et al, ; Olivares‐Pulido et al, ).…”
Section: Resultssupporting
confidence: 88%
“…The comparison between electron density values measured by COSMIC and those modeled by using H Linear testifies that it is possible to accurately reproduce the ionospheric topside electron density profile by using a semi-Epstein layer with a scale height linearly dependent on height, at least from hmF2 to about 800 km of height. This largely agrees with previous works using a Chapman function with height-varying scale height [2], [38]- [40].…”
Section: B Calculation Of the Topside Scale Height Through Cosmic/fosupporting
confidence: 92%
“…In Liu et al () a 5% of questionable profiles have been identified; in Brunini et al, (), about 20% points have been eliminated after applying a quality filter. More recently, the importance of having selection criteria to eliminate doubtful profiles has been underlined by Uma et al, () and an example of a specific filtering procedure has been suggested by Hernández‐Pajares et al ().…”
Section: Introductionmentioning
confidence: 99%